Hematúria. - A Milheiro; R Prisco (Acta Médica Portuguesa, 1999)
Patients referred for hematuria work-up are frequently seen in the urologic practice. The initial evaluation does not require the participation of a urologist or nephrologist, due to the false sense of security in the evaluation of an asymptomatic and persistent hematuria. In fact, an adequate history and physical followed by urinalysis and radiologic tests, such as IVP and ultrasonography, must be made in the initial evaluation to exclude any serious urologic/nephrologic disease.